Right to Information, Judicial Activism and the Rule of Law: The Case of Indonesia's Mining Litigation - Safitri, Myrna Asnawati (Brawijaya Law Journal, 2018)
The right to information is fundamental in environmental protection. Lack of access to information regarding environmental planning and licensing has often lead to public interest environmental litigation. The right to information is also an element in the formation of the rule of law in both its formal and substantive aspects. Mining must be cautionary conducted due to its high potential for environmental damage and pollution. This paper discusses the extent to which is the right to environmental information protected in Indonesia through several cases of mining litigation. Using statutory and court cases methods, it discusses laws on the rights to information in general and in the field of environmental protection, how Indonesian courts have interpreted the government obligations to fulfill citizens' access to mining information, and the extent to which that legal interpretation contributes to the rule of law elements. This paper then concludes that the right to mining information is still difficult to attain. Public bodies tend to prioritize formal-procedural aspects in providing information and setting up a public consultation. However, the cases studied indicate that judicial activism has provided corrections to such a procedural approach. More substantive rule of law principles used by the courts to interpret mining zones and environmental permits procedures.